Exploring the Antidepressant-like Effects of Wogonin: Analysis of Behavioural, Neurochemical, and Biochemical Parameters - Pannu, Arzoo; Goyal, Ramesh K. (Current Bioactive Compounds, 2025)
BackgroundWogonin, a bioactive compound isolated from S. barbata D. Don, has been identified in the literature as a potential inhibitor of monoamine oxidase (MAO), a key enzyme involved in the degradation of neurotransmitters associated with mood regulation. This study aims to investigate the antidepressant-like activity of wogonin in vivo, utilizing a preclinical model. The rationale for selecting wogonin stems from its documented MAO inhibitory properties, suggesting a potential role in modulating neurotransmitter levels implicated in depressive disorder.MethodsThe study employs a multifaceted approach, incorporating behavioural, neurochemical, and biochemical assessments. The Chronic Unpredictable Mild Stress model is utilized to induce depression-like behavior in rodents for 21 days. Two doses of wogonin (20 and 40 mg/kg per orally) and standard (fluoxetine, 20 mg/kg, and imipramine, 15 mg/kg) were administered to albino mice. Behavioural paradigms, including the Tail Suspension Test, Forced Swim Test, and Open Field Test, are employed to assess the impact of wogonin on depressive-like symptoms on the 21st day. Neurochemical analyses focus on alterations in 5-HT, NE, and DA levels within relevant brain regions, and MAO activity is quantified to ascertain wogonin's potential as an MAO inhibitor on the 22nd day. Biochemical assessments emphasize wogonin's antioxidant properties and its ability to mitigate oxidative stress, a significant factor in depression pathophysiology. Plasma nitrite levels are measured to elucidate wogonin's impact on nitric oxide signalling. Plasma corticosteroid levels are also quantified to delineate wogonin's effect on the hypothalamic-pituitary-adrenal (HPA) axis, a central regulator of stress response.ResultsWogonin demonstrates significant antidepressant effects in a dose-dependent manner in the behavioural assessments, showing a marked reduction in depressive-like behaviours across all paradigms. Neurochemical analyses revealed a significant (p £ 0.05) restoration of monoamine neurotransmitter levels in the relevant brain regions as compared to CUMS-induced stress group. Additionally, wogonin exhibits a potent (p £ 0.05) inhibitory effect on MAO activity. Biochemical assessments demonstrate a significant (p £ 0.05) increase in antioxidant capacity and a reduction in oxidative stress markers. Plasma nitrite levels indicate an enhancement of nitric oxide signalling. Corticosteroid levels showed a modulation of the HPA axis, suggesting a regulatory effect on stress response.ConclusionThis comprehensive study establishes wogonin as a promising MAO inhibitor with notable antidepressant potential. The findings provide crucial insights into its mechanisms of action, indicating a multifaceted approach to alleviating depression. Wogonin's demonstrated efficacy across behavioural, neurochemical, and biochemical parameters presents a strong foundation for further research and development of wogonin-based antidepressant interventions.
Keywords: depression